2017
DOI: 10.3892/mco.2017.1337
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a pharmacist outpatient service for S-1 adjuvant chemotherapy in patients with gastric cancer

Abstract: Abstract. S-1 adjuvant chemotherapy is an outpatient treatment for gastric cancer. To evaluate the role of the pharmacist outpatient service in increasing medication adherence and reducing adverse events associated with S-1, the present study retrospectively analyzed prescription recommendations from pharmacists to physicians and the persistence rate of S-1 adjuvant chemotherapy use in patients with gastric cancer. A total of 40 subjects who utilized the pharmacist outpatient service between November 2014 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…We established an ambulatory care pharmacy practice for HCV-infected outpatients receiving IFN-free DAA therapy in September 2014, when we started therapy with DAAs in Kobe City Medical Center General Hospital. The purposes of establishing this practice were to provide information to physicians for appropriate prescriptions and to patients for the resolution of unclear points, to minimize the potential influence of drug-drug and drug-food interactions, to prevent adverse drug events, to enhance the patients’ adherence, and to maximize the effectiveness of IFN-free DAA therapy through patient education and counseling on DAA treatments [ 10 , 11 ]. The DAA therapy includes daclatasvir tablets and asunaprevir capsules (DCV + ASV), sofosbuvir/ledipasvir combination tablets (SOF/LDV), ombitasvir/paritaprevir/ritonavir combination tablets (OBV/PTV/r), and elbasvir tablets and grazoprevir tablets (EBR + GZR) for HCV genotype 1-infected patients and sofosbuvir tablets and ribavirin tablets or capsules (SOF + RBV), and OBV/PTV/r tablets and ribavirin capsules (OBV/PTV/r + RBV) for HCV genotype 2-infected patients.…”
Section: Methodsmentioning
confidence: 99%
“…We established an ambulatory care pharmacy practice for HCV-infected outpatients receiving IFN-free DAA therapy in September 2014, when we started therapy with DAAs in Kobe City Medical Center General Hospital. The purposes of establishing this practice were to provide information to physicians for appropriate prescriptions and to patients for the resolution of unclear points, to minimize the potential influence of drug-drug and drug-food interactions, to prevent adverse drug events, to enhance the patients’ adherence, and to maximize the effectiveness of IFN-free DAA therapy through patient education and counseling on DAA treatments [ 10 , 11 ]. The DAA therapy includes daclatasvir tablets and asunaprevir capsules (DCV + ASV), sofosbuvir/ledipasvir combination tablets (SOF/LDV), ombitasvir/paritaprevir/ritonavir combination tablets (OBV/PTV/r), and elbasvir tablets and grazoprevir tablets (EBR + GZR) for HCV genotype 1-infected patients and sofosbuvir tablets and ribavirin tablets or capsules (SOF + RBV), and OBV/PTV/r tablets and ribavirin capsules (OBV/PTV/r + RBV) for HCV genotype 2-infected patients.…”
Section: Methodsmentioning
confidence: 99%
“…In view of the RDI, some studies have demonstrated that insufficient RDI of chemotherapy was related to a poor prognosis in some malignancies such as breast, ovarian, colon, and pancreatic cancers [2730]. In GC, two studies suggested that a decreased RDI of S-1 will lessen the efficacy of S-1 adjuvant chemotherapy for GC and may lead to a poor prognosis [31, 32]. Our present study included only patients with stage II or III GC who received sufficient adjuvant chemotherapy with S-1 after surgery and excluded patients with very advanced metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…There were nine studies that met our inclusion criteria with a total of 3496 participants (Table 1). 4,9,14,[24][25][26][27][28][29] The studies included 945 females and 1108 males, with one study of 1443 patients not reporting on the breakdown of these patients. The included studies had a weighted mean (SD) age of 60.8 (11.4).…”
Section: Included Studiesmentioning
confidence: 99%
“…In total, five studies followed a pre-and post-intervention design, 4,9,26,27,29 one study was a cohort study, 24 one study was a single arm historical cohort study 25 and two were randomised controlled trials. 14,28 All studies completed the initial pharmacist intervention face-to-face.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation